Nineteen - Angkko, 1983- (Drawn & Quarterly, 2020)
"Ancco looks back at her own tumultuous adolescence, from the not-so-distanced lens of a twenty-something. A mother's struggles mirror her teen's. Memories of care between the cartoonist and her grandmother--before her faculties had started to fade. Quick judgments look ugly through the eyes of a teen, who's leaning into her own sense of self. Whether it's friends, family, animals, or even a stranger on the internet, the stories in Nineteen exude generosity and love, while being steeped in the malaise and distractions of youth"--P. [4] of cover.